Предмет: Алгебра,
автор: Аноним
Помогите пожалуйста .
Приложения:
Ответы
Автор ответа:
0
(1+a)/(3-a)(3+a)+(a+2)/a(a+3)=(a+a²+3a-a²+6-2a)/[a(3-a)(3+a)]=
=(2a+6)/[a(3-a)(3+a)]==2(a+3)/[a(3-a)(3+a)]=2/a(3-a)
a=5
2/(5*(-2))=-0,2
=(2a+6)/[a(3-a)(3+a)]==2(a+3)/[a(3-a)(3+a)]=2/a(3-a)
a=5
2/(5*(-2))=-0,2
Автор ответа:
0
Спасибо !!!
Похожие вопросы
Предмет: Биология,
автор: Brimir
Предмет: История,
автор: goltcevapolina
Предмет: Қазақ тiлi,
автор: angelinabossova
Предмет: Алгебра,
автор: TARAM3210
Предмет: Литература,
автор: Adelya13579